Health Education as An Effort to Increase Knowledge and Control Behavior of Hypertension in Hypertensive Elderly - Supatmi, Supatmi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Elderly people experience various health problems, especially those related to the aging process such as hypertension, cancer, mental disorders and other degenerative diseases which are increasing. Health education is a planned effort to change the behavior of individuals, groups, or communities from unhealthy to healthy behavior. The aim of the research was to determine the effect of health education on knowledge about hypertension and behavior to control hypertension in hypertensive elderly at Posyandu for the Elderly at Matahari Kepek Timbulharjo Sewon Bantul Yogyakarta. This type of research is pre-experimental research with a one group pretest posttest approach. The population in this study was 60 elderly people. The sample was carried out using a purposive sampling method. The number of respondents in the study was 30 in accordance with predetermined criteria. Data was taken using a questionnaire sheet. The instrument knowledge questionnaire about hypertension in the elderly with results validity test results were > 0.361 and reliability results 0.938. In the behavioral questionnaire, the validity test results were > 0.361 and the reliability results were 0.904. Data were analyzed using the Wilcoxon statistical test. Based on the bivariate test of hypertension education with increased knowledge, a sig value of 0.000 <0.05 was obtained and health education with hypertension control behavior was 0.000. So it can be concluded that there is a significant influence of health education on knowledge and behavior of controlling hypertension in the elderly at Posyandu Lansia Matahari Kepek Timbulharjo Sewon Bantul Yogyakarta.